2015
DOI: 10.32738/jeppm.201507.0002
|View full text |Cite
|
Sign up to set email alerts
|

 A Procurement Performance Model for Construction Frameworks

Abstract: Collaborative construction frameworks have been developed in the United Kingdom (UK) to create longer term relationships between clients and suppliers in order to improve project outcomes. Research undertaken into highways maintenance set within a major county council has confirmed that such collaborative procurement methods can improve time, cost and quality of construction projects. Building upon this and examining the same single case, this research aims to develop a performance model through identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Such contractual measures are supported by KPIs from site inspections and publication of performance results. The contract based KPIs were found to be very effective performance measures for control of time for civil engineering frameworks by Lam and Gale (2015). Bresnen and Marshall (2000) and Morledge et al (2021) 'Competence of suppliers' relating to past performance was also identified by the regression analysis to be a significant driver for the project outcome of cost.…”
Section: Multiple-case Study and Causal Relationshipsmentioning
confidence: 99%
“…Such contractual measures are supported by KPIs from site inspections and publication of performance results. The contract based KPIs were found to be very effective performance measures for control of time for civil engineering frameworks by Lam and Gale (2015). Bresnen and Marshall (2000) and Morledge et al (2021) 'Competence of suppliers' relating to past performance was also identified by the regression analysis to be a significant driver for the project outcome of cost.…”
Section: Multiple-case Study and Causal Relationshipsmentioning
confidence: 99%
“…Operational financial incentives coupled with advanced contracting methods could improve both commitment and motivation within projects. In a case study of the civil engineering frameworks in a county council in the South East region, Lam and Gale (2015) decided that incentive mechanisms could be linked to key performance indicators (KPIs) enabling focus upon the client's outcomes through financial incentives. Framework suppliers prefer the chance of winning further work rather than individual project bonuses and the framework agreement examined reflected this choice.…”
Section: Performance Drivers In the Procurement Processmentioning
confidence: 99%
“…Therefore, the success of construction projects is essential. A construction project is called successful, when it is completed within the time, cost, and quality specified at the beginning of the project (Lam and Gale, 2015). Among these three factors, quality is a competitive factor in constructions (Lawson, 2013), such quality maintenance and control in constructions, results in creating long-term competitions and business survival (Tan and Abdul, 2005).…”
Section: Quality In the Construction Industrymentioning
confidence: 99%